PEMETAAN PROSES BISNIS UNTUK MEMUDAHKAN PENILAIAN KINERJA KOPERASI; STUDI KASUS PADA KOPERASI NELAYAN: Studi Kasus Pada Koperasi Nelayan - Akhmad Yunani; Ery Supriyadi; Trida Gunadi; Deddy Supriyadi (INTEKNA informasi teknik dan niaga, 2020)
Fishermen cooperative is expected to be an economic entity that plays a significant role in enhancing welfare of fishermen. Through the cooperatives, fishermen are having opportunities to scale-up their resources and strengthen their position in the fishery supply chain system. Using a fishermen cooperative (the co-op) as a case, this study aims to build business process map in order to facilitate the assessment of co-op’s performance. The map is developed based on the data collected mainly by observation and interview with the board of the cooperative. The study reveals that the cooperative has no both clear pattern of business process and measured performance. The study proposes the business process map with clear pattern so that the performance of the co-op can be measured objectively. The co-op needs to be accompanied and supervised by strongly related stakeholders (in particular the Government) in an attempt apply the map. The map will be more favourable if there is a further research on developing supply chain model of the cooperatives.